Chiral recyclable fluorous disulfonamide ligand for catalytic enantioselective cyclopropanation of allylic alcohols. Issue 45 (11th November 2015) - Kawashima, Yuya; Ezawa, Tetsuya; Yamamura, Mai; Harada, Taisuke; Noguchi, Takuya; Miura, Tsuyoshi; Imai, Nobuyuki
Abstract: Allylic alcohols reacted with Et2 Zn and CH2 I2 in the presence of a catalytic amount of fluorous disulfonamide 3a to afford the corresponding cyclopropylmethanols in 69%-quantitative yields with 49–85% ee. Recovery of the fluorous ligand 3a was readily performed from the reaction mixture by the fluorous solid-phase extraction (FSPE), and the recovered 3a could be reused without a significant loss of the catalytic activity and enantioselectivity. Graphical abstract: